Convergência de elites: a sustentabilidade no mercado financeiro - Sartore, Marina de Souza (2010)
The launch of the Brazilian Corporate Sustainability Index in Sao Paulo s Stock Market, analyzed through an economic approach, can be reduced to a new financial tool which measures the profitability of Sustainable listed companies. However, through a sociological approach, the launch of this index is equivalent to the creation of the Brazilian Socially Responsible Investment Market. The creation of this market demonstrates the emergence of new polarizations in the Economic Field, particularly in the Financial Field. These new polarizations indicate a change in the Financial Field, which presents a new way of thinking the Financial Market based on taking account of social, environmental and financial criteria. This change emerges from an elite convergence which challenges the limits of the Financial Field, at the same time trying to reinvent the Financial Market through a proposal of a Sustainable Capitalism. This thesis indicates that it s possible to understand the creation of Socially Responsible Investment Market by studying the actors and institutions that participate in the Corporate Sustainability Index s Committee. As a result, this study emphasizes the urge of developing a Sociology of Indexes. At last, this thesis concludes that the Sustainability insertion in the Financial Field is legitimated by a group acting in the financial area, which converges with the Corporate Social Responsibility s and The Environmental Movement s elite, in an attempt to turn the table of mainstream finance. However, this mainstream turn does not push towards the ending of financial market, but it s strengthening instead.